Management of Demand Uncertainty Within MRPIIUsing Possibility Theory - Geneste, Laurent; Grabot, Bernard; Reynoso-Castillo, Gabriel (My University, 2005)
In order to closely adapt what they produce to what will be sold, it is mandatory for nowadays companies to make early decisions on the base of an uncertain production planning. We suggest a way to explicitly model the uncertainty and imprecision of the demand using possibility theory, all along the MRPII steps: Material Requirement Planning, Load Planning, Scheduling. Though propagation of this uncertainty, the “Fuzzy-MRP” method aims at providing a richer information to decision makers, based on a quantification of the various situations that may arise according to the possible variations of the customer's demand.